Malaysian dental therapists' job motivation, job satisfaction, intention to leave and perceived future roles. Issue 2 (9th January 2022) - Zakaria, Noor Azhani; Ab‐Murat, Norintan; Che Musa, Muhd Firdaus
Abstract: Objective: To assess Malaysian dental therapists' job satisfaction, motivation, turnover intention and perceived future roles, following recent changes in the regulations that allow them to provide dental care within their scope of practice in the private sector. Methods: A self‐administered questionnaire was distributed to public dental therapists who were selected using a stratified random sampling technique. Questions included items on social structure, job satisfaction and motivation (based on the Warr‐Cook‐Wall scale), turnover intention (based on four cognitive processes) and perceived future roles. Multiple logistic regression was used to assess the predictors of dental therapists' turnover intention. Results: Overall, a majority (>90%) of the participants had high job satisfaction and job motivation, with total mean scores of 45.70 ± 6.86 and 21.16 ± 2.63, respectively. A total of 8.3% intended to leave the public sector to work in a different organization. Of those who chose to remain as a dental therapist in the next five years, only 7% considered working in the private sector. The significant predictors for turnover intention were educational attainment, years of working experience, job satisfaction level and future preferred working sector. Conclusion: Although the newly introduced Dental Act allows dental therapists to expand their roles to the private setting, very few intended to do so. This could be related to them having a high level of job satisfaction and job motivation while serving in the public sector.